Development of Topical/Transdermal Self-Emulsifying Drug Delivery Systems, Not as Simple as Expected - Daniélle van Staden; Jeanetta du Plessis; Joe Viljoen (MDPI AG, 2020)
Self-emulsifying drug delivery systems (SEDDSs) originated as an oral lipid-based drug delivery system with the sole purpose of improving delivery of highly lipophilic drugs. However, the revolutionary drug delivery possibilities presented by these uniquely simplified systems in terms of muco-adhesiveness and zeta-potential changing capacity lead the way forward to ground-breaking research. Contrarily, SEDDSs destined for topical/transdermal drug delivery have received limited attention. Therefore, this review is focused at utilising principles, established during development of oral SEDDSs, and tailoring them to fit evaluation strategies for an optimised topical/transdermal drug delivery vehicle. This includes a detailed discussion of how the authentic pseudo-ternary phase diagram is employed to predict phase behaviour to find the self-emulsification region most suitable for formulating topical/transdermal SEDDSs. Additionally, special attention is given to the manner of characterising oral SEDDSs compared to topical/transdermal SEDDSs, since absorption within the gastrointestinal tract and the multi-layered nature of the skin are two completely diverse drug delivery territories. Despite the advantages of the topical/transdermal drug administration route, certain challenges such as the relatively undiscovered field of skin metabolomics as well as the obstacles of choosing excipients wisely to establish skin penetration enhancement might prevail. Therefore, development of topical/transdermal SEDDSs might be more complicated than expected.